Pola Komunikasi Guru dan Murid SMA SLB-B Dharma Wanita di Sidoarjo - Nabila Mega Putri (DIGICOM : Jurnal Komunikasi dan Media, 2022)
This study aims to determine the communication patterns and communication barriers of high school teachers to high school students with particular limitations in hearing (deaf). The literature review in this study is the communication patterns and communication patterns of teachers and students. The communication pattern has three directions to understand the application of communication between teachers and students. This type of research is descriptive qualitative, where the source of the data is obtained through interviews with informants or sources. The subjects in this study were two high school teachers, namely Syaiful as the homeroom teacher for class 12 and Bambang as the homeroom teacher for class 10, and two high school students of Dharma Wanita Inclusive School in Sidoarjo named Nasya and Imam. Data collection techniques by observation and interviews. The technique used in this research is qualitative analysis, namely qualitative data obtained from informant interviews and observations, which will provide an overview of the teacher-student communication process. The conclusion of the study, the teachers and high school students at Dharma Wanita Inclusive School in Sidoarjo have applied Linear, Primary, and secondary communication patterns as well as two-way and multidirectional communication patterns of teachers and students in communicating with their students. Meanwhile, in terms of communication barriers, it can be concluded that teachers and high school students at Dharma Wanita Inclusive School in Sidoarjo often experience socio-cultural, prejudice, environmental, and semantic obstacles in communicating with students but can overcome them.